Forging Excellence Amid Transition: The Moderating Effect of Green Innovation on the Financial Performance of Coal-Fired Power Plants (PLTU) in Indonesia - Affardi, Chirmala Wisnu Permata; Salamah, Robiatus; Taufiqurrahman, Mohammad Aviciena; Izza, Risa Aulia; Rivera, Hofifah (Dinasti Publisher, 2026)
This study analyzes the moderating role of green innovation in the relationship between environmental pressure and the financial performance of Coal-Fired Power Plants (PLTU) in Indonesia. Amid an increasingly inevitable energy transition, the coal-fired power plant industry, which accounts for approximately 60% of the nation’s generating capacity and is responsible for nearly 40% of greenhouse gas emissions faces multidimensional pressure from regulators, investors, and the public. This study employs a qualitative approach using a case study design focused on PT IPL. Data were collected through in-depth interviews with the Finance Manager, Environmental Manager, and local residents living near the Coal-Fired Power Plant (PLTU), supported by document analysis and field observations. The research findings indicate that green innovation serves as a significant moderating variable in transforming environmental costs into sustainable economic value. Investments in pollution control technologies, biomass co-firing programs, and improvements in thermal efficiency do indeed reduce short-term profit margins. Investments in pollution control technology, biomass co-firing programs, and improvements in thermal efficiency do indeed put pressure on short-term profit margins. However, green innovation mitigates this relationship through three main channels, namely enhanced reputation, which expands access to sustainable financing at competitive interest rates; strengthened investor confidence, which increases corporate value; and enhanced social legitimacy, which reduces the risk of conflict and operational disruptions. Companies that integrate green innovation into their core business strategies through transparent reporting and proactive communication demonstrate greater financial resilience. This study concludes that green innovation is a strategic variable that moderates the transformation of environmental challenges into competitive advantages; thus, a company’s ability to leverage it will determine its success in balancing short-term profitability and long-term sustainability in the era of energy transition.